2020
DOI: 10.3390/nu12051281
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Effects of Commercial Prebiotic GOS and FOS Products on Human Colonic Caco–2 Cells

Abstract: Prebiotic oligosaccharides are widely used as human and animal feed additives for their beneficial effects on the gut microbiota. However, there are limited data to assess the direct effect of such functional foods on the transcriptome of intestinal epithelial cells. The purpose of this study is to describe the differential transcriptomes and cellular pathways of colonic cells directly exposed to galacto-oligosaccharides (GOS) and fructo-oligosaccharides (FOS). We have examined the differential gene expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 88 publications
0
17
1
Order By: Relevance
“…From all our data we can speculate that in DSS treated cells, GOS was able to counteract the inflammatory status and the membrane barrier damage induced by inflammatory cytokines that reverted to control level. The ability of GOS to regulate immune response was previously suggested, as it has been shown to be effective in modulating cytokine secretion in intestinal cells through TLR4 binding ( 56 ), as well as through a direct effect on intestinal cell transcriptome by modulating the expression of several genes, including some involved in antimicrobial activity and inflammatory response ( 36 ). According to previous studies, our results strongly suggest that a specific prebiotic can have a direct effect on the regulation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From all our data we can speculate that in DSS treated cells, GOS was able to counteract the inflammatory status and the membrane barrier damage induced by inflammatory cytokines that reverted to control level. The ability of GOS to regulate immune response was previously suggested, as it has been shown to be effective in modulating cytokine secretion in intestinal cells through TLR4 binding ( 56 ), as well as through a direct effect on intestinal cell transcriptome by modulating the expression of several genes, including some involved in antimicrobial activity and inflammatory response ( 36 ). According to previous studies, our results strongly suggest that a specific prebiotic can have a direct effect on the regulation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro models, GOS has also been shown to modulate the epithelial barrier function by inducing differentiation and epithelial wound repair, and by promoting the growth of specific gut bacteria, associated with changes in SCFA profiles ( 35 ). The effect of GOS on epithelial cells has been further confirmed by a transcriptomic analysis performed on Caco-2 cells, showing that GOS was able to modulate the expression of several genes implicated in digestion and transepithelial transport, which contribute to intestinal cell integrity and function ( 36 ).…”
Section: Introductionmentioning
confidence: 89%
“…Medium was changed every second day. After 20 days, cells were treated in accordance with the experiments of Lafontaine et al (2020) for 24 h with HG, GM, LGM, or (as a control) with a sugar mixture (galactose, glucose and lactose [1/1/1, w/w/w]) and at a concentration of 25 mg ml −1 ( Zenhom et al, 2011 ). After this incubation, cells were visually inspected, medium was removed, cells were washed twice with ice-cold deionized H 2 O, snap frozen in liquid nitrogen to quench cell metabolism, and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…70,71 Many studies have demonstrated that microorganisms and dietary components influence the regulation of the TJ protein expression. 72,73 Pattern recognition receptors (PRRs), which are widely expressed by the intestinal epithelial cells and intestinal immune cells, play an important role in the regulation of barrier integrity and TJ expression. 74,75 Toll-like receptors (TLRs) are the most well-studied PRRs, among which TLR2 and TLR4 are the best studied due to their interaction with gut bacteria and dietary components and their ability to mediate epithelial barrier integrity.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…129 In another study, exposure of Caco-2 cells to GOS of DP2-7 (1.4% w/v) also showed the ability to improve the integrity of the tight junction via increasing the trans-epithelial electrical resistance (TER). 73 More recently, the transcriptome of epithelial Caco-2 cells was fully characterized after stimulation with GOS and the hMO sialyllactose (SL) and the effects on the epithelial barrier function were studied by investigating cellular pathways involved in cell proliferation, differentiation, and re-epithelialization. GOS modulated 63 pathways of the epithelial barrier transcriptomes, among which the top 4 most significantly modulated pathways were influenced in the same way by the hMO SL, indicating a similarity in function between GOS and SL.…”
Section: Effects Of Gos On Pathogen Adhesionmentioning
confidence: 99%